Relationship between reading and long-term storage and retrieval (Glr) in college students. Issue 2 (4th March 2019) - Avitia, Maria Jesus; Kaufman, Alan S.; Bray, Melissa; Kaufman, James C.
ABSTRACT: The purpose of this study was to (a) identify the relationship between specific types of reading ability, different forms of learning, and long-term memory and retrieval ( Glr) ; and then (b) to determine the degree to which self-assessed reading ability and a Glr measure could predict objective reading ability. College students were administered three different reading assessments from the Kaufman Test of Educational Achievement, Second Edition (KTEA-II): word reading, reading comprehension, and nonsense word decoding. They were also given two pairs of Glr subtests that consisted of immediate and delayed versions from the Kaufman Assessment Battery for Children, Second Edition (KABC-II). One set was embedded within context, whereas the other was not. Results showed that although overall reading ability and reading comprehension correlated the highest with Glr measures that were embedded in context, word reading, and nonsense word decoding were correlated the highest with delayed measures of Glr . Second, the self-assessment accounted for 23% of the variability in overall reading ability. Not only do these results show the strength of the relationship between Glr and reading, but also the ability to use these measures along with self-assessment to screen for reading disabilities.